Knowledge, attitudes, and practice of final year nursing students on risk factor of cardiovascular disease in Universiti Sains Malaysia - Manan, Nurizzati (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Cardiovascular disease (CVD) is a leading cause of death in Malaysia. Major risk factors of CVD were modifiable. Therefore, CVD is a preventable disease through lifestyle modification. The current study was conducted to determine the knowledge on CVD risk factor, attitude towards CVD risk reduction and practice in preventing occurrence of CVD of final year nursing students in Universiti Sains Malaysia. This is a cross-sectional study using simple random sampling. Final year nursing students were selected in this present study. The respondents were randomly selected using randomizer. The sample size was 85. Knowledge, attitude and practice questionnaire was adopted from the previous study done in Kuantan. The mean and standard deviation of the knowledge, attitude and practice scores were (x: 13.41, SD: 1.458), (x: 55.06, SD: 4.241), (x: 23.6471, SD: 4.1539) respectively. No significant differences were found between attitude towards CVD risk reduction and practice in preventing occurrence of CVD (p=1.000). From the findings, USM nursing students should engage more in exercise and developing healthy lifestyle.